THE EFFECT OF COMMUNICATION AND MANAGERIAL SUPPORT ON PERFORMANCE WITH ORGANIZATIONAL CULTURE AS A MODERATING VARIABLE IN THE TREASURY DIVISION OF PLN HEAD OFFICE - Rini Andriani; Kiki Farida Ferine; Muhammad Isa Indrawan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of organizational culture, communication, and managerial support on employee performance, with communication and organizational culture as moderating variables. The study was conducted at the Treasury Division of PLN Head Office with a population of 270 employees, all of whom were sampled through a census technique. The research method used a quantitative approach with Structural Equation Modeling analysis techniques based on Partial Least Square (SEM-PLS) through SmartPLS software. The results showed that organizational culture, communication, and managerial support had a positive and significant effect on employee performance. However, the moderating effect of communication and organizational culture on the relationship between independent variables and performance was not significant. These findings emphasize the importance of the role of strong organizational culture, effective communication, and managerial support in improving employee performance, especially in a complex work environment such as PLN. This study also provides theoretical contributions to the development of human resource management science, as well as practical suggestions for organizational management in the electricity sector.